The effects of low-level laser therapy on muscle strength and functional outcomes in individuals with knee osteoarthritis: a double-blinded randomized controlled trial - Amornthep Jankaew; Yu-Lin You; Tai-Hua Yang; Yu-Wei Chang; Cheng-Feng Lin (Scientific Reports, 2023)
Abstract The purpose of this study was to compare the therapeutic effects of low-level laser therapy (LLLT) with 808 and 660 nm wavelength on muscle strength and functional outcomes in individuals with knee osteoarthritis (OA). A total of 47 participants were randomly assigned to the 808 nm, 660 nm, and sham control groups. Two LLLT groups received continuous LLLT with a mean power of 300 mW in different wavelengths at the knee joint 15 min a session three days per week for eight weeks, while the control group received the sham LED treatment. The knee strength and functional performance involving 30-s sit-to-stand, 40 m fast-paced walk, stair climbing, and the TUG test were measured at the baseline and one week after the interventions were completed. The results showed that knee extensor strength was more improved in the 808 nm group as compared to the 660 nm group (p < 0.001, d = 0.57) and the sham control (p < 0.001, d = 0.40), while increased flexor strength was demonstrated in the 808 nm (p = 0.009, d = 0.67) and sham control groups (p < 0.001, d = 0.97). The number of 30-s sit-to-stand was increased only in the 660 nm group (p = 0.006, d = 0.49). All three groups exhibited improvements in the other three functional performance-based tests after the interventions with no statistically significant differences among the groups. In conclusion, both intervention groups improved muscle strength and functional performance as compared to the control group. The 808 nm wavelength group showed better results in knee extensor strength. Therefore, laser therapy is suggested to be integrated into rehabilitation programs to improve muscle strength and functional performance in the population with knee OA.